Sinterização de matrizes cerâmicas à base de alumina reforçadas por carbetos a partir de precursores poliméricos - Diniz, Marcus Alexandre (2007)
Ceramic composites produced with polymerics precursors have been studied for many years, due to the facility of obtaining a complex shape, at low temperature and reduces cost. The main objective of this work is to study the process of sintering of composites of ceramic base consisting of Al2O3 and silicates, reinforced for NbC, through the technique of processing AFCOP, as well as the influence of the addition of LZSA, ICZ and Al as materials infiltration in the physical and mechanical properties of the ceramic composite. Were produced ceramic matrix composites based SiCxOy e Al2O3 reinforced with NbC, by hidrosilylation reaction between D4Vi and D1107 mixtured with Al2O3 as inert filler, Nb and Al as reactive filler. The specimens produced were pyrolised at 1200, 1250 and 1400°C and infiltred with Al, ICZ and LZSA, respectively. Density, porosity, flexural mechanical strength and fracture surface by scanning electron microscopy were evaluated. The microstructure of the composites was investigated by X-ray diffraction to identify the presence of crystalline phases. The composites presented apparent porosity varying of 31 up to 49% and mechanical flexural strength of 14 up to 34 MPa. The infiltration process improviment of the densification and reduction of the porosity, as well as increased the values of mechanical flexural strength. The obtained phases had been identified as being Al3Nb, NbSi2, Nb5S3, Nb3Si and NbC. The samples that were submitted the infiltration process presented a layer next surface with reduced pores number in relation to the total volume